Market Efficiency and Risk Premium in the Turkish Wholesale Electricity Market - Yilmaz, Mustafa Kemal; Kucukcolak, Necla I.; Kucukcolak, R. Ali (International Journal of Energy Economics and Policy, 2018)
Due to the nature of electricity, prices in the wholesale electricity market show great variation according to the hours of the day. Thus, it is important for market participants to forecast hourly prices to give accurate orders. This study covers the analysis of hourly electricity prices by referring to the relationship between spot and forward prices and volume in the Turkish market over two sub-periods of dual pricing: December 2011-May 2016 and June 2016-December 2017. The latter period is characterized by the implementation of a new trading algorithm in the market. The results reveal that forward prices behave as unbiased predictors of spot prices, most of the time. Remarkably, evolution of the difference between spot and forward prices, namely risk premium, depicts that the spot price supports the arbitrage opportunities in the electricity market. The introduction of the new trading algorithm does not depict significant effect on the risk premium. Keywords: Electricity Market Efficiency, Day-Ahead Market, Forward Prices, Risk Premium JEL Classifications: G10, G13, Q40, Q49